Pesantren Between Learning and Moral Agents of Community Character Formation - M. Zainul Umam (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is motivated by the phenomenon that occurs in society, namely (1) the younger generation who have poor character in terms of ethics, (2) the lack of optimal educational institutions in instilling values, ideals and motivations that will encourage the younger generation to have a good personality, (3) Lack of knowledge of parents on how to shape the character of the child in order to have a good personality in terms of ethics. Pondok Pesantren Raudlatul Muta'allimin Jagalan 62 Langgardalem Kudus has a curriculum that prioritizes character education in the learning process. The research method used is a descriptive method with a qualitative approach to further explore the core of research problems with data collection techniques using interviews with managers, teaching and students as objects of education. The theories referenced in this study include the theory of character education, the theory of management of educational institutions pondok pesantren, and the concept of education outside the school